2021
DOI: 10.1021/acsomega.0c05581
|View full text |Cite|
|
Sign up to set email alerts
|

Indole-3-acetamides: As Potential Antihyperglycemic and Antioxidant Agents; Synthesis, In Vitro α-Amylase Inhibitory Activity, Structure–Activity Relationship, and In Silico Studies

Abstract: Indole-3-acetamides (1–24) were synthesized via coupling of indole-3-acetic acid with various substituted anilines in the presence of coupling reagent 1,1-carbonyldiimidazole. The structures of synthetic molecules were elucidated through different spectroscopic techniques including electron ionization-mass spectroscopy (EI-MS), 1H-, 13C NMR, and high-resolution EI-MS (HREI-MS). These compounds were screened for their antihyperglycemic and antioxidant potentials. All compounds displayed good to moderate inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Thus, the elevated blood glucose level was considered hyperglycemia . α-Amylase is responsible for the hydrolysis of complex polysaccharides into small oligosaccharides, and α-glucosidase finally converts all into glucose to be absorbed in the bloodstream …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the elevated blood glucose level was considered hyperglycemia . α-Amylase is responsible for the hydrolysis of complex polysaccharides into small oligosaccharides, and α-glucosidase finally converts all into glucose to be absorbed in the bloodstream …”
Section: Resultsmentioning
confidence: 99%
“…The consequences of SAR studies explained that compounds (4-(4methylphenyl)piperazin-1-yl)(5-methoxy-1H-indol-2yl)methanone (81.63 %), and (5-fluoro-1H-indol-2-yl)(4-(4hydroxyphenyl)piperazin-1-yl)methanone (85.6 %) had equivalent DPPH free radical scavenging activity as compared to standard drug Vitamin E (88.6 %). Khan et al [87] reported the synthesis and antioxidant activity of several aryl-substituted indole-3-acetamides (46). All the synthesized compounds evaluated for their antioxidant activity and result were exhibited good to moderate activity.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The 2,3‐dimethyl and 2,4‐dimethyl substituted indole derivatives exhibited high antidiabetic activity with IC 50 values 9.46±0.03 and 9.37±0.03 μM respectively in comparison with the reference drug acarbose 37.38±0.12 μM. Khan et al [87] . accounted the synthesis and antidiabetic property of various aryl‐substituted indole‐3‐acetamides ( 46 ).…”
Section: Bioactivity Evaluationmentioning
confidence: 99%
“…The antioxidant properties of melatonin are probably due to the presence of the C-3 ethylamido side chain [ 14 ]. Also, synthetic indoles, bearing substitutes at the C-3 positions, are promising antioxidant agents [ 14 , 15 , 16 , 17 ]. Our previous study showed that gramine substituted by the pyrrolidinedithiocarbamate moiety has significant antioxidant properties [ 18 ].…”
Section: Introductionmentioning
confidence: 99%